2012
DOI: 10.1002/glia.22445
|View full text |Cite
|
Sign up to set email alerts
|

G protein‐coupled receptor 30 contributes to improved remyelination after cuprizone‐induced demyelination

Abstract: Estrogen exerts neuroprotective and promyelinating actions. The therapeutic effect has been shown in animal models of multiple sclerosis, in which the myelin sheath is specifically destroyed in the central nervous system. However, it remains unproven whether estrogen is directly involved in remyelination via the myelin producing cells, oligodendrocytes, or which estrogen receptors are involved. In this study, we found that the membrane-associated estrogen receptor, the G protein-coupled receptor 30 (GPR30), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 56 publications
2
22
0
1
Order By: Relevance
“…In the CNS, activation of ER β may promote remyelination of oligodendrocytes in the mouse model of MS via upregulation of AKT/mTor signaling [28, 44]. In addition, activation of GPR30 was also found to improve CNS remyelination by oligodendrocytes [45]. Previous studies demonstrated that primary SCs expressed both ER α and β [46].…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, activation of ER β may promote remyelination of oligodendrocytes in the mouse model of MS via upregulation of AKT/mTor signaling [28, 44]. In addition, activation of GPR30 was also found to improve CNS remyelination by oligodendrocytes [45]. Previous studies demonstrated that primary SCs expressed both ER α and β [46].…”
Section: Discussionmentioning
confidence: 99%
“…As Gpr17 is enriched in white matter plaques of MS patients and in rodent models of MS, antagonism of Gpr17 or other inhibitory GPCRs may indeed be efficacious in future treatment strategies [57,64,66,67]. Additional GPCRs have been implicated in CNS myelin repair including Cxcr4, Gpr30, endothelin receptors, and sphingosine 1-phosphate receptors [81][82][83][84][85], underscoring the importance of this receptor super-family in myelin health and disease.…”
Section: Pharmacological Implications Of Gpcrs In Myelin Diseasesmentioning
confidence: 99%
“…Although many important estrogenic responses are mediated by the 2 nuclear ERs ERα and ERβ [7], increasing evidence suggests that the nongenomic effects mediated by GPER1 signaling play crucial roles in mouse models of various human inflammatory disorders [17,18,19,20,21], where the receptor mainly shows an anti-inflammatory role. However, although there have been almost 900 publications on GPER1 since its discovery in the early 2000s and its expression in immune cells has been described [37], the in vivo role of GPER1 in the regulation of neutrophil function still remains enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GPER1 knockout mice models reveal no reproductive deficits but multiple physiological alterations and a lack of estrogen-mediated effects in numerous tissues, including those of the immune system [15]. In addition, GPER1 activation has been shown to mediate anti-inflammatory protective effects in rodent models of multiple sclerosis [16,17,18] and ischemia-reperfusion injury [19,20,21]. These findings suggest that GPER1 could be a potential target for new therapies against a range of inflammatory or autoimmune diseases which display gender dimorphism as a result of the regulation of physiological and immunological processes by sex steroids [3].…”
Section: Introductionmentioning
confidence: 99%